QUANTITATIVE EASING THE FED MENJADI SENTIMEN PENGGERAK INDEKS HARGA SAHAM GABUNGAN ATAU JAKARTA COMPOSITE INDEX - Nugroho, Arif (Jurnal Akuntansi AKUNESA, 2013)
The purpose of this research is analyzing Indonesian capital market reaction, uses jakarta composite index (IHSG) and quantitative easing issue announcement that indicated with level indeks changes of jakarta composite index (IHSG). This research explored the issue by applying one methods of analysis: the event study methodology for analyzing the market reactions and statistical differences caused by event quantitative easing issue issue announcement. Samples of this research consist of indeks level of jakarta composite index began at 31 Oktober 2008 and finish at 15 Maret 2013. Level indeks changes used to measure market reaction. The results of this research level indeks changes for date quantitative easing issue announcement positive and significant. Further, this study found some significant differences level indeks changes between pre and post event day. In other word, quantitative easing issue announcement containing the meaningful information (information content) for investor. Keyword: Quantitative easing, capital market, and IHSG